Family of users of a psychosocial attention center: a comprehensive analysis in Schütz - preview note - Marcio Wagner Camatta; Jacó Fernando Schneider (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Introduction: Because of the recent advances reached by Brazilian Psychiatric Reform movement, it becomes important to evaluate the alternative services, amongst them, the Psychosocial Attention Centers (CAPS), in the family of the user's point of view about these services. Objective: Understanding the perception of the user's family about a CAPS, concerning to the team work. Methodology: The study follows a qualitative and phenomenological approach. After the approval of the ethics committee, data collection was made in "CAIS Mental Centro" CAPS, in Porto Alegre city, Rio Grande do Sul State, during October and November, 2006, with the following guiding question: "Talk about the work of the team of CAIS Mental Centro - Psychosocial Attention Center." Results: We carried through 13 interviews with the familiars that were more interested in the treatment of the user. Information analysis will be developed according to the comprehensive interpretation, from the following analysis categories: social everyday, intersubjectivity, typification, social relations and social action. So, we will search for the comprehension on how the familiar one experience the work of the team in a CAPS, using as support the phenomenological sociology of Alfred Schütz. Conclusion: We will deepen the analysis later, however, we can stand out that this research will be important because it will be able to contribute for the improvement of the mental health assistance of the users and families that use the CAPS, beyond serving as knowledge source for the construction of possible actions in mental health.